Analysis of a nuclear localization signal in the p14 splicing factor in Trypanosoma cruzi - Westergaard, Gaston G. (2010)
There are only a few reported nuclear localization signals (NLS) in trypanosomes despite intensive research on nuclear metabolic processes such as mRNA processing and transcription during the recent past. Moreover, there are only two reports for a monopartite (La protein) and bipartite (H2B histone, ESAG8) NLS in Trypanosoma brucei. We decided to investigate a NLS in Trypanosoma cruzi by selecting p14, a small RNA recognition motif (RRM) containing protein involved in the splicing process in the nucleus. Its small size (117 amino acids), and an optimized streamlined workflow for analysis in T. cruzi, allowed us to define a region of basic amino acids (RRKRRR) located at the C-terminus that is necessary for nuclear localization. However, the NLS for p14 appeared to be more complex since the signature RRKRRR alone is necessary but not sufficient to direct heterologous proteins, such as GFP, to the nucleus. Since p14 interacts strongly with splicing factor SF3b155, a much larger protein, we designed a p14 variant unable to interact with it. The results allowed us to discard the notion that p14 is entering the nucleus, or is retained within, as the sole consequence of being part of a larger complex. Extensive mapping showed that all of the information for nuclear import resides within the small p14 protein in a bipartite NLS composed of the signature RRKRRR and a region of the RRM domain. Thus, NLS definition in T. cruzi is more complex than previously described.